Effects of Different Fertilizer Regimes on the Growth of ‘Merawan Siput Jantan’ (Hopea Odorata Roxb.) for Urban Landscape - Mohd. Noor, Ahmad Azaruddin (2007)
Fertilizer application is fundamental in providing adequate nutrients to landscape trees planted in and around urban areas. However, little information is available on the nutrient requirements of urban landscape trees especially on forest species planted for landscaping in Malaysia. An observation was carried out to examine the growth and nutrient status of Hopea odorata planted for urban landscape at the New Klang Valley Expressway (NKVE) on disturbed and undisturbed soils. Significant (p < 0.05) difference in total tree height, foliar nitrogen content and relative chlorophyll content was found between trees planted on disturbed and undisturbed soil. Limited availability of nitrogen (N) due to poor soil condition could be one of the reasons for the unsatisfactory growth of H. odorata on disturbed and cut soil. A fertilizer experiment was carried out to determine the effect of different fertilizer regimes as remedial treatment on H. odorata on cut and disturbed soil at the study site. The experiment employed a factorial design plus control in Randomized Complete Block Design (RCBD). The treatments comprised of two types of fertilizer, two nitrogen rates in the form of compound fertilizer, two frequencies of application and a control. Result after twelve months of treatment indicated that types of fertilizer, nitrogen rates and frequencies of application affected the growth of H. odorata at the study site. Organic fertilizer AvantiTM (3.5 N : 4.5 P : 2.5 K : 1.0 Mg) gave significantly (p < 0.05) higher height and crown diameter increments, specific leaf area (SLA), net photosynthesis (Pn), apparent quantum yield (Qn) water use efficiency (WUE) and light use efficiency (LUE) than inorganic fertilizer Nitrophoska YellowTM (15 N : 15 P : 6 K : 4 Mg). Fertilizer combinations with higher N rate at 150 g N/year (1000 g Nitrophoska YellowTM and 4286 g AvantiTM) was found to give significantly (p < 0.05) higher height and crown diameter increments, SLA, leaf area index (LAI), foliar nitrogen (N) content, relative chlorophyll content and net photosynthesis (Pn) regardless of types of fertilizer and frequencies of application. The study showed that application of fertilizer at 4 times per year gave significant effect (p < 0.05) on total height increment and foliar N of H. odorata. All fertilizer combinations were found to give no significant effect (p < 0.05) on foliar phosphorus (P) as well as foliar potassium (K) content of H. odorata. The results further indicated that treatment combination of organic fertilizer with 150 g N (4286 g AvantiTM) applied 4 times per year gave the best response where significant (p < 0.05) difference with unfertilized control plot were observed in growth parameters of H. odorata with the exception of stem diameter (dbh) increment. It was also found to give significantly (p < 0.05) higher foliar N content, relative chlorophyll content, LAI, Pn, maximum assimilation (Amax) Qn and LUE than control.